李光耀 ：1978年以来中国人的新加坡印象 = Lee Kuan Yew : the image of Singapore in post-1978 China - 陈纳慧 Chen, Nahui (2017)
我的博士论文讨论中国人观念中的李光耀。新加坡前总理李光耀被认为是现代新加坡之父，他一手打造了新加坡奇迹。然而，李光耀的领导权威和退位后的余威并不止于新加坡的内政外交，他对中国、亚洲和世界亦有着令人瞩目的影响力，长久不散。本论文将透过中国人如何看李光耀这一视角，来对中国的发展、 中新关系和东西势力角逐做出新的阐释。我的研究主要回答这三个问题：中国人与新加坡华人之间的同文同种究竟在中新关系之间起到了怎样的作用？在向他国取经以探寻中国未来发展道路时，中国的政治精英为何特别亲睐于李光耀的威权统治，他们又是如何解读和建构新加坡模式的？李光耀如何在中国与亚洲区域、中国与西方之间扮演多面性角色的？我得出的主要结论为：不同于通常所认为的种族亲缘性有助于促进国家间的关系，同文同种往往正是国家间冲突和矛盾的根源。李光耀对中国和对世界的意义远远超越了他与新加坡重合的部分。中国人观念中的李光耀图谱不仅讲述了李光耀和他的新加坡的故事，也反映了中国自身发展的变迁和国际政治的风云变幻。 My dissertation is a study of the Chinese perception of Lee Kuan Yew (LKY), the man who in a variety of ways and for so many years defined Singapore. It seeks to develop a new interpretation of China’s domestic development, Sino-Singapore relationship, and East-West power relations, through the lens of LKY. It addresses these questions: What was the real role played by the ethnic affinity between the Chinese Singaporeans and the Chinese of China, in shaping Sino-Singapore relations during LKY’s time? Why has LKY’s authoritarian leadership which is illustrated by the so called Singapore Model drawn China’s special attention? How did he play a multi-faceted role between China and the rest of Asia, and between China and the West. Main arguments drawn from my study are: Under certain conditions ethnic affinity between two peoples can lead to antagonism instead of cooperation. The multi-faceted role of LKY in both China’s domestic development and in the international arena, which leads to his prevailing influence in China, is far beyond his overlap with Singapore. The Chinese ideological landscape regarding LKY not only tells the story of LKY and his Singapore, but also reflects China’s political rearticulation and the continuingly changing world politics.